Back Cover: Morphological Control of Heteroleptic cis‐ and trans‐Pd2L2L′2 Cages (Angew. Chem. Int. Ed. 28/2017). Issue 28 (29th May 2017) - Bloch, Witold M.; Holstein, Julian J.; Hiller, Wolf; Clever, Guido H.
Abstract : Integrative self‐sorting of palladium(II) metal ions and banana‐shaped ligands is driven by the interplay of complementary ligand geometries to form cis‐ or trans ‐[Pd2 L 2 L′ 2 ] heteroleptic cage structures (1 –3 in the picture). In their Communication onpage 8285 ff., G. H. Clever and co‐workers report a topologically unprecedented "doubly bridged figure eight" assembly in which one of the ligands is forced to adopt an anti conformation. The extent of the geometric constraints in the heteroleptic cage system is further demonstrated through highly selective ligand‐substitution reactions.